Multi-Scale Factors Promote Entomophilous Pollination: Productive Blueberry Agroecosystems as a Study Model - Cavigliasso, Pablo; Maza, Noelia; Barreto, Carolina G.; Maina, M.E.; Gennari, Gerardo Pablo; Chacoff, Natacha Paola (Wiley, 2025)
Blueberry cultivation requires insect-mediated pollination for optimal fruit formation. Studies have shown that improving the efficiency of pollen exchange during flowering increases both the quantity and quality of fruit. Blueberry flowers have a unique anther structure that facilitates pollen release through a specialised interaction called ‘buzz pollination’, which is performed by wild bee species rather than Apis mellifera. The study aims to assess the effects of pollination management, weed management, and landscape heterogeneity on pollinator communities, and their interaction with the crop and blueberry fruit set. Nine blueberry plots were studied to investigate the influence of including Bombus pauloensis hives, the presence of inter-row vegetation, and landscape heterogeneity on pollinator abundance, richness, visitation rate, and fruit production. Generalised linear mixed models (GLMM) were used to analyse the relationship between these factors. No significant differences in fruit formation were found between plots receiving pollination services from Apis mellifera and those with a combination of A. mellifera + B. pauloensis hives. However, inter-row vegetation had a positive effect on pollinator abundance and visitation rate to blueberry flowers. The increase in cultivated areas had a negative effect on the visitation rate of both managed and native pollinators. Conversely, more diverse landscapes had a negative and significant effect on A. mellifera abundance within the plots. These findings suggest the importance of implementing wild pollinator-friendly management practices, carefully assessing honeybee densities, and managing resources at both local and landscape scales to enhance bee visitation and blueberry fruit production.